Reconstruction Of Extensor Apparatus Of Knee By Gracilis - Dr. J.K. Sinha; Dr. K.K. Mangal (Indian Journal of Plastic Surgery)
Marginal excision, wide excision with radieal resection, hip disarticulation and hemipelvectomy are the operative modalities in vogue for the surgical management of lower extremity sarcomas. Leiomyosarcoma of lower one third of thigh is treated by wide excision and resultant defect is filled by gracilis transposition technique.